Avaliação das condições higiênico-sanitárias da produção de refeições à base de carne da alimentação escolar no município de Natal-RN - Rosa, Monique Silveira (2008)
The National School Nutrition Program is the oldest program in the country directed at food and nutrition safety. Its aims are to offer nutritional food as a supplement to students of public and philanthropic schools. Studying school nutrition transcends the investigation as a purely social program, given that it reaches the fields of public health, nutrition and food, using a wide variety of approaches. Thus, it is characterized by a multidisciplinary study, where the disciplines work side by side in distinct aspects of a single problem. Aim: This study aims to assess hygiene practices during the preparation of meat-based meals in public schools in the city of Natal, Brazil. Methods: A list was applied at 27 schools to identify the procedures of good food preparation practices. In addition, cooking and meal distribution temperature were measured and a microbiological analysis of the final preparation and of the water used in preparing it was performed. For microbiological analyses of the food, we analyzed coliforms at 45°C, coliforms at 35°C and Enterococcus, and for the water, we analyzed thermotolerant coliforms and total coliforms, using the methods recommended by APHA, 1995. Results: Most of the schools did not meet the required standards in all the variables related to good food preparation practices, except for the time spent preparing the meat, in which 89% were within the norm. Cooking temperature of the meals was within the standard; however, the temperature at distribution and the time spent dispensing the meals were inadequate. Of the 27 schools, 22 (81.5%) showed the presence of coliforms at 35° C in at least one meal sample and 18 (66.7%) had values above the recommended limit for coliforms at 45°C. The presence of E. coli was identified in 6.1% of the samples analyzed. The presence of Enterococcus was not found at any of the schools. With respect to the water, the North district of the city was the only one that did not meet the standards for the two indicators evaluated. The contamination found was not associated with the hygiene or food storage problems observed. Conclusions: The results show that the hygiene-sanitary conditions of meat-based public school meals were unsatisfactory, demonstrating the need for improvements in the production process to preserve the health of the student population. Multidisciplinarity: Researchers from the areas of food microbiology, nutrition, public health and statistics took part in this study, a decisive factor for characterizing the research as multidisciplinary